Almada: texto(s) em vários tempos de leitura - Silva, Celina (2018)
Re-writing of some sequences of Da Histoire du Portugal par Coeur, ao Encontro da Ingenuidade, concerning the two versions of Histoire du Portugal par Coeur, written by Almada Negreiros at Paris in 1919, according to some new data, regarding mainly the articulation of literature, drawing and dance.